The Influence of Good Corporate Governance Mechanism on Earnings Management: Empirical Study in Indonesian Stock Exchange Listed Company for Periods of 2006-2010 - Hermiyetti, Hermiyetti; Manik, Evita Nora (The Indonesian Capital Market Review, 2013)
The purpose of this research is to examine the influence of good corporate governance mechanism about earnings management in companies listed in Indonesian Stock Exchange during 2006 to 2010. The independent variables include the size of commissioner board, independent commissioner board percentage, size of audit committee, and commissioner meeting frequency. The dependent variable is earnings management which is measured by discretionary revenue model (Stubben, 2010). Size of company is used as the control variable in this research. The population of this research is 465 samples from companies listed at Indonesian Stock Exchange during 2006 to 2010. The sampling method used in this research is purposive sampling method. In addition, the data analysis method used is regression analysis and descriptive statistics. The result of this research indicates that the mechanism of good corporate governance which is represented by the size of commissioner board, independent commissioner board percentage, size of audit committee, and commissioner meeting frequency do not have any significant impact on earnings management. However, the result shows that company size gave positive influence toward earning management.